The Influence of Village Funds on Poverty in Wakatobi Regency: A Village-Level Study - Permatasari, Fimia Firda; Muizzuddin Fazaalloh, Al (Journal of Development Economic and Social Studies, 2026)
Poverty in archipelagic regions remains a persistent challenge, particularly in remote island regencies where geographic barriers and fiscal limitations constrain development outcomes. This study aims to analyse the effect of Village Funds on poverty at the village level in Wakatobi Regency. Employing a quantitative approach through a Fixed Effects Model with cluster-robust standard errors, this research utilises village-level panel data to examine fiscal and structural determinants of poverty. The findings indicate that Village Funds have not consistently reduced village poverty, a pattern attributed to the formula-based allocation mechanism and the shift in budget priorities during the Covid-19 pandemic. Structural factors including population density and the Geographical Difficulty Index (Indeks Kesulitan Geografis/IKG), are found to play a significant role in shaping village poverty dynamics. Furthermore, the results reveal considerable heterogeneity across islands, suggesting that the effectiveness of village fiscal policy is strongly influenced by local geographic and demographic conditions. These findings imply that poverty reduction strategies in archipelagic regions require a more integrated and context-sensitive approach, with greater emphasis on strengthening local economic capacity rather than relying solely on uniform fund distribution mechanisms.